Antimicrobial Photodynamic Approach in the Inactivation of Viruses in Wastewater: Influence of Alternative Adjuvants - Maria Bartolomeu; Cristiana Oliveira; Carla Pereira; M. Graça P. M. S. Neves; M. Amparo F. Faustino; Adelaide Almeida (MDPI AG, 2021)
Pathogenic viruses are frequently present in marine and estuarine waters, due to poor wastewater (WW) treatments, which consequently affect water quality and human health. Chlorination, one of the most common methods used to ensure microbiological safety in tertiarily treated effluents, may lead to the formation of toxic chemical disinfection by-products on reaction with organic matter present in the effluents. Antimicrobial photodynamic therapy (aPDT) can be a promising disinfecting approach for the inactivation of pathogens, without the formation of known toxic by-products. Additionally, some studies have reported the potentiator effect on aPDT of some compounds, such as potassium iodide (KI) and hydrogen peroxide (H2O2). In the present study, the aPDT efficiency of a PS formulation constituted of five cationic porphyrins (Form) in the inactivation of E. coli T4-like bacteriophage, a model of mammalian viruses, in different aqueous matrices with different organic matter content, was evaluated. Photoinactivation studies were performed at different concentrations of Form and in the presence of the adjuvants KI and H2O2. The results showed that the efficiency of bacteriophage photoinactivation is correlated with the Form concentration, the amount of the organic matter in WW, and the adjuvant type. Form can be an effective alternative to controlling viruses in WW, particularly if combined with H2O2, allowing to significantly reduce PS concentration and treatment time. When combined with KI, the Form is less effective in inactivating T4-like bacteriophage in WW.